Opportunities and Challenges of Rural Entrepreneurship in Afghanistan - YAR, Fayaz Gul Mazloum; HAJINEJAD, Ali (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose: Rural entrepreneurship, as a fundamental and parallel approach to rural development goals, can significantly contribute to the advancement and progress of rural areas. It aims to reduce unemployment, enhance the productivity of individuals and resources, increase income, improve the economic situation, and empower rural communities. Therefore, it is considered a suitable and effective strategy for accelerating rural development. This paper explores the challenges and opportunities of rural entrepreneurship in Afghanistan.Methodology:In order to do this, a library-documentation research strategy was used, and a thorough literature study of pertinent topics and areas was carried out.Findings: As a result of this research, challenges such as a lack of financial resources, inadequate infrastructure facilities, and sociocultural barriers, as well as opportunities like affordable land, abundant natural landscapes and resources, and local customs and traditions, were identified.Implication:Finally, a framework for promoting rural entrepreneurship is proposed, and recommendations for addressing challenges and using opportunities better.